2005
DOI: 10.1080/13547500500272614
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to pesticides: analysis of human placental acetylcholinesterase, glutathione S-transferase and catalase as biomarkers of effect

Abstract: Pre- and perinatal exposure to pesticides is deleterious on foetal and neonatal development, but information regarding possible effects on environmental low-dose exposure to pesticides is scarce. Most epidemiological studies of the health effect of pesticides have been based on self-reported information. However, detailed information on past pesticide use is difficult to reconstruct. This is a current study conducted among pregnant mothers attending a delivery care and perinatal programme at a public hospital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 57 publications
3
12
0
2
Order By: Relevance
“…Previous analysis of blood samples of these women when they were pregnant demonstrated that they had been environmentally exposed to OP pesticides during PP (Souza et al 2005). Considering that the volume of OP pesticides applied in the area has decreased since this study was performed, the results obtained strengthen the importance of biomonitoring for intervention and the need to focus on long-term effects of prolonged exposure in this population.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous analysis of blood samples of these women when they were pregnant demonstrated that they had been environmentally exposed to OP pesticides during PP (Souza et al 2005). Considering that the volume of OP pesticides applied in the area has decreased since this study was performed, the results obtained strengthen the importance of biomonitoring for intervention and the need to focus on long-term effects of prolonged exposure in this population.…”
Section: Discussionsupporting
confidence: 62%
“…The strongest winds from west and south-west occur in spring. The participants selected had participated in a previous study of placental biomarkers of exposure to OP in relation to newborn parameters (Souza et al 2005). They were all living near an agricultural area where insecticides, mainly OPs such as azinphos-methyl, phosmet, chlorpyrifos, and dimethoate, are applied during the PP, 6 months a year, during dry seasons: spring and summer (September to February).…”
Section: Population and Study Areamentioning
confidence: 99%
“…However, differential effects on AChE placental activity have been observed (Table 2). A single cutaneous dose of OP decreased placental AChE activity in rats (AbuQare & Abou-Donia, 2001) whereas when the activity of placental AChE in residents of rural communities exposed to OP was studied, the average AChE activity obtained in placentas collected during the pulverization season was significantly higher than in those collected during the non-pulverization period (Souza et al, 2005). This latter result was later confirmed in two biomonitoring assays performed in our laboratory in subsequent years on the same population.…”
Section: Level Of Effectsupporting
confidence: 64%
“…NFKB1 is activated in preeclampsia, and by oxidative stress in a trophoblast-like cell line (Vaughan and Walsh, 2012). Acetylcholinesterase (ACHE) is localised in many regions including the placenta , where it plays a significant role in pesticide effects on foetal development (Souza et al, 2005). A splice variant of the Rett syndrome protein MECP2 regulates placental development (Itoh et al, 2012) and the translation initiation factor eIF4E prevents final extravillous M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 15 trophoblast cell differentiation and supports placental cell proliferation and survival (Kawamura et al, 2011;Kitroser et al, 2012)The kinesin KIF17 is highly expressed in the developing vascular endothelium in early pregnancy (Sati et al, 2009) and the synaptic scaffold protein SHANK2 is also localised in the placenta and one of a group of imprinted genes where expression patterns distinguish between new-born neurobehavioral profiles (Green et al, 2015) Respiratory Cilia DYX1C1 (dyslexia susceptibility 1 candidate 1) is involved in the regulation of respiratory cilia that sweep mucus, debris and noxious particles away from airways.…”
Section: The Androgen Receptor (Ar) Is Localised In Cells Involved Inmentioning
confidence: 99%